Comparison of Rates of and Charges from Pregnancy Complications in Users of Extended and Cyclic Combined Oral Contraceptive (COC) Regimens: A Brief Report - Howard, Brandon (2013)
OBJECTIVE: Evaluate pregnancy complication rates and related charges in users of 84/7, 21/7, and 24/4 combined oral contraceptives (COCs). STUDY DESIGN: Data were obtained from the i3 InVision Data Mart(™) retrospective claims database. Subjects were aged 15–40 years; first prescribed a COC between 1/1/2006 and 4/1/2011; and continuously insured for ≥1 year. 84/7 users were matched 1:1 to 21/7 and 24/4 users. RESULTS: Pregnancy-related complication rates and associated charges were significantly lower with 84/7 vs. 21/7 and 24/4 regimens. CONCLUSION: Preliminary data suggest 84/7 regimens may be associated with fewer pregnancy complications and lower related charges.